2012
DOI: 10.1016/j.ajpath.2012.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Eph/Ephrin Signaling in Injury and Inflammation

Abstract: The Eph/ephrin receptor-ligand system plays an important role in embryogenesis and adult life, principally by influencing cell behavior through signaling pathways, resulting in modification of the cell cytoskeleton and cell adhesion. There are 10 EphA receptors, and six EphB receptors, distinguished on sequence difference and binding preferences, that interact with the six glycosylphosphatidylinositol-linked ephrin-A ligands and the three transmembrane ephrin-B ligands, respectively. The Eph/ephrin proteins, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
150
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(154 citation statements)
references
References 99 publications
4
150
0
Order By: Relevance
“…21,22 Our data suggest that the inhibition of ephrinB2/EphB4 does not enhance inflammation after ischemia ( Figure XI in the online-only Data Supplement).…”
Section: Ephrinb2 Activation Leads To Reduced Damage In Brain Tissuementioning
confidence: 87%
“…21,22 Our data suggest that the inhibition of ephrinB2/EphB4 does not enhance inflammation after ischemia ( Figure XI in the online-only Data Supplement).…”
Section: Ephrinb2 Activation Leads To Reduced Damage In Brain Tissuementioning
confidence: 87%
“…Analysis of the low frequency variants identified EPHA6 as the gene most significantly associated with paclitaxel-induced neuropathy ( (15)(16)(17) and also belonged to the high-neuropathy risk group of genes (Table 3). In EPHA5, 5 carriers had high neuropathy versus 1 with low neuropathy; and in EPHA8, 9…”
Section: Gene-based Analysis Of Paclitaxel-induced Neuropathy In the mentioning
confidence: 99%
“…CYP2C8*3 (12)(13)(14), CYP3A4*22 (7), TUBB2A rs909964 and rs909965 (8,9)) influence neuropathy risk, while genome wide genotyping has uncovered novel genes (10,11). A GWAS by our group (11) suggested that the EPHA gene family, which plays a key role in the development of nervous system and in nerve injury repair (15)(16)(17), was a key player for paclitaxel neuropathy susceptibility. Meta-analysis of GWAS top hits showed that EPHA5 rs7349683 reached genome-wide significance (11), and follow-up studies further supported that this variant (18), EPHA6 rs301927 (9,18) and EPHA8 rs209709 (18) moderately increased paclitaxel-induced neuropathy risk.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Moreover, aberrant expression or activation of Eph receptors and ephrins is believed to contribute to malignant or pathologic states in epithelial tissues. [9][10][11][12]14,20 This review focuses on the role of Eph receptor and ephrin signaling in epithelial tissues that undergo extensive regeneration and remodeling in adults, including those present in the breast, gastrointestinal tract, and skin.…”
Section: Introductionmentioning
confidence: 99%
“…Eph receptor and ephrin signaling has been shown to play a prominent role during embryogenesis, but a growing body of evidence indicates that adult epithelial tissues are another major site for Eph receptor and ephrin ligand action. [9][10][11][12][13][14] Epithelial tissues line body surfaces and cavities. They are composed of single (simple) or multiple (stratified) layers of epithelial cells that are tightly anchored to the underlying basement membrane and one another via specialized junctional complexes; these include integrin-based adhesion complexes for cell-extracellular matrix anchorage points while adherens junctions, desmosomes, tight junctions, and gap junctions are found at cell-cell contacts.…”
Section: Introductionmentioning
confidence: 99%